Issue Framing and Institutional Constraints in EU Agenda-Setting: an Analysis of European Union Sport Policy - Borja Garcia; Mads de Wolff; Serhat Yilmaz (Journal of Contemporary European Research, 2018)
The article uses agenda-setting to analyse the process which saw sport included in the new EU programme, Erasmus+, despite cuts in the EU’s budget. In doing so, the article addresses gaps in two bodies of literature. On the one hand, it contributes to developing the study of EU agenda-setting. On the other hand, the article analyses recent developments in EU sport policy, a body of literature that has not paid attention yet to decisions taken after the entering into force of the Treaty of Lisbon (2009). The article applies conceptually guided process tracing through written documents and 25 semi-structured interviews with representatives from the European Commission, European Parliament and the Council of the European Union. The analysis shows how the Commission overcame blockades by framing sport initiatives as part of the wider agenda on economic growth through education, training and participation in grassroots sport, thus obtaining a funding stream for a new policy area in a time of austerity measures. The research illustrates that agenda-setting is a useful conceptual framework for explaining not just radical but also incremental policy changes on the EU agenda.